SAT0747-HPR Can achieving sustained das remission prevent progression of sub- clinical atherosclerosis? a prospective cohort study in early rheumatoid arthritis (ERA). (15th June 2017) - Mak, WY; Shang, Q; Lau, XSL; Lee, AP-W; Yu, CM; Li, EK-M; Wong, PCH; Tam, LHP; Kwok, KY; Yip, ML; Pang, HT; Lao, VW-N; et al.
Abstract : Background: Patients with rheumatoid arthritis (RA) have higher incidence of cardiovascular disease (CVD) and prevalence of arterial stiffness (AS) due to underlying inflammation. Effective immunosuppression using anti-TNF was shown to improve AS in early RA (ERA) patients.Whether it is a specific effect by blocking the TNFα pathway or suppression of inflammation remains uncertain. While achieving Disease Activity Score in 28joints (DAS) remission was associated with significant benefits in articular disease, its effect on co-morbidities such as CVD risk is uncertain. Objectives: To investigate the effect of achieving sustained DAS remission on AS. Methods: This randomized control trial investigates the effect of 2 tight-control treatment strategies aiming 1.Simplified disease activity score [SDAI≤3.3]or 2.minimal disease activity [DAS<2.6] on AS in ERA patients.120 patients with active disease (DAS≥3.2), symptoms onset <2years and bDMARDs naive were recruited and received 1-year treatment.Treatment are adjusted based on the standardized protocol every 3month aiming at either 1 of the 2 targets. AS is measured by branchial-ankle pulse wave velocity (baPWV) using a dedicated tonometry system (Omron VP-2000). Results: In the interim analysis, results of 100 patients [male (23.0%); 52.8±13 years] completed 1year follow-up were analyzed. No significant differences between groups in clinical features, DMARD use and baPWV at month12 (M12) was observed yet significant improvement in disease activity was found in both groups.Hence, results from the 2 groups were combined to ascertain if achieving sustained DAS remission can prevent AS progression.The disease activity improved significantly [DAS: 4.8 (4.2, 5.6) at baseline (BL) vs 2.38 (1.6, 3.0) at M12, p <0.001]. 57% patients achieved DAS remission at M12 and 36% patients achieved DAS remission over 3 consecutive visits (sustained remission). No significant differences were found in disease activity, cardiovascular risk factors (CRF) and baPWV at BL between groups who can (CA) or cannot achieve (NA) sustained remission. At M12, no significant differences in CRF and baPWV were found between groups.However, the change in baPWV was significantly different between CA and NA group [-65.5 (-147.25, 44.0) cm/s vs 39 (-65.25, 124.75) cm/s, p =0.005]. The differences remained significant in the %change of baPWV [-4.4 (-9.67–2.84)% vs 2.51 (-4.34–10.28)%, p =0.006].I n univariate analysis, assocation of change in baPWV and potential predictors included BL baPWV, blood pressure (systolic & diastolic) and sustained DAS remission was found.By multivariate analysis, achieving sustained DAS remission was an independent predictor for baPWV reduction. Conclusions: Effective suppression of inflammation by achieving sustained DAS remission may prevent progression of AS in ERA patients. Disclosure of Interest: None declared